Activity of digestive enzymes in chicken's small intestine and caeca: Effect of dietary protein and carbohydrate content - Ciminari, María E. (2014)
Digestion is a mediating factor between the animals and their environment, one of the variables related to the efficiency in extracting energy from nutrients is rate of hydrolysis. Phylogenetical and functional hypothesis has been proposed linking dietary flexibility and enzyme lability. Species belong to Parvclass Galloanserae, studied until now, did not modulate aminopeptidase-N activity but they did modulate disaccharidases activities. Additionally, peptide hydrolysis has been demonstrated in avian caeca, but not in chickens. Finally, dietary proteins are essential for chicken growth in the first stages of development, but little information is available in chickens beyond 42 days of life. Chickens beyond that age were fed for 15 days either a high protein (DHP = 49.72% protein and 11.92% carbohydrates) or a high starch diet (DHS = 52.82% carbohydrates and 10.49% protein). Aminopeptidase-N, maltase and sucrase, were assessed in chicken’s small intestines and caeca. Body mass of DHP birds was 37.5% higher than body mass of DHS birds, at the end of the trial. Aminopeptidase-N and sucrase did not change, but maltase exhibited higher activity in DHS than in DHP birds. The lack of aminopeptidase-N modulation and its relatively high activity in caeca, together with a modulation of maltase, contribute and give apparent support to the functional hypothesis. Surprisingly, a high quantity of protein resulted important for growth in chickens after 42 days of life. Also it is important to notice that a casein diet has been demonstrated as a high digestible meal for chickens, so the last data may be of interest for poultry industry.